Truss bridge movement and displacement analysis for different types of earthquake loadings - Fatin Nabihah, Suhaime (2017)
Today we often heard news about earthquake that happen in Malaysia. So a study of earthquake was carrying out for structural which is bridge structure. Bridge structure is the critical structure that will damage cause by the seismic effect and also an important structure. Most bridges in Malaysia does not take account the seismic loading. Therefore, by using SAP 2000 software a modal analysis was created and the purpose of this research is to study the dynamic characteristic of each structure. The dynamic characteristic includes displacement, acceleration and velocity of the bridge structure. The critical and weak point for each member of the structure can be determined through the displacement and the acceleration value. The earthquake data is from Acheh and El-Centro earthquake that get from the Malaysia Meteorological Department. 12 mode shape had been shown after analyse the structure. Each mode shape produces the different number of frequency and also natural time period. According to 12 mode shape produced, three mode shapes with the highest frequency will be selected as the best mode shape. Other than that the rigidity of shape of each mode shape also can be determined according to the classification of time period the building. The classification are Rigid (T < 0.3 sec), Semi-Rigid (0.3 sec < T < 1 sec), and Flexible Structure (T > 1)